Association of susceptible genotypes to periodontal disease with the clinical outcome and tooth survival after non-surgical periodontal therapy: A systematic review and meta-analysis - Chatzopoulos, Georgios Sokratis; Doufexi, Aikaterini Ellisavet; Kalogirou, Fotini (My University, 2016)
Background: The real clinical utility of genetic testing is the prognostic value of genetic factors in the clinical outcome of periodontal treatment and the tooth survival. A meta-analysis was undertaken to estimate the effect of a susceptible genotype to periodontitis on the clinical outcomes of non-surgical periodontal therapy and the tooth survival.Material and Methods: A systematic search of MEDLINE-Pubmed, Cochrane Library and Scopus was perfor- med. Additionally, a hand search was done in three journals. No specific language restriction was applied. Two reviewers screened independently titles and abstracts or full text copies. Quality assessment of all the included studies was held.Results: Initial screening of electronic databases resulted in 283 articles. Ten studies met the inclusion criteria, nine of them examined the clinical outcome, while the other one investigated the tooth survival in susceptible individuals after non-surgical periodontal therapy. Eight of included studies were selected for the meta-analysis. IL-1 positive genotypes increase the risk of tooth loss, while no association found between the bleeding on pro- bing (BOP), clinical attachment loss (CAL) and plaque index (PI) with the genotype status. Probing pocket depth (PPD) reduction in the first three months and in long-term results found to have a significant association with the genotype. Conclusions: There is no difference in the clinical measurements after non-surgical periodontal treatment, apart from PPD. More publications are needed to identify a cause-effect relationship.
Keywords: Clinical outcome; Genotype; Meta-analysis; Periodontal disease; Periodontal therapy; Periodontitis; Polymorphism; Susceptibility; Systematic review; Tooth loss